Generated SecPen_NY-ESO-1_ubiquitin-pulsed dendritic cell cancer vaccine elicits stronger and specific T cell immune responses - Yunkai Yang; Xiaohan Guo; Bo Hu; Peng He; Xiaowu Jiang; Zuohuan Wang; Huaxing Zhu; Lina Hu; Minghua Yu; Meiqing Feng (Elsevier, 2021)
Dendritic cell-based cancer vaccines (DC vaccines) have been proved efficient and safe in immunotherapy of various cancers, including melanoma, ovarian and prostate cancer. However, the clinical responses were not always satisfied. Here we proposed a novel strategy to prepare DC vaccines. In the present study, a fusion protein SNU containing a secretin-penetratin (SecPen) peptide, NY-ESO-1 and ubiquitin was designed and expressed. To establish the DC vaccine (DC-SNU), the mouse bone marrow-derived DCs (BMDCs) were isolated, pulsed with SNU and maturated with cytokine cocktail. Then peripheral blood mononuclear cells (PBMCs) from C57BL/6 mice inoculated intraperitoneally with DC-SNU were separated and cocultured with MC38/MC38NY-ESO-1 tumor cells or DC vaccines. The results show that SNU was successfully expressed. This strategy made NY-ESO-1 entering cytoplasm of BMDCs more efficiently and degraded mainly by proteasome. As we expected, mature BMDCs expressed higher CD40, CD80 and CD86 than immature BMDCs. Thus, the PBMCs released more IFN-γ and TNF-α when stimulated with DC-SNU in vitro again. What's more, the PBMCs induced stronger and specific cytotoxicity towards MC38NY-ESO-1 tumor cells. Given the above, it demonstrated that DC-SNU loaded with SecPen and ubiquitin-fused NY-ESO-1 could elicit stronger and specific T cell immune responses. This strategy can be used as a platform for DC vaccine preparation and applied to various cancers treatment.